Analisis Pengaruh Brand Knowledge dan Online consumer review Terhadap Minat Berkunjung Pada Kafe Naughty Little Cat Park - Ismunandar, Adam; Sulhaini, Sulhaini (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study aims to examine the influence of brand knowledge and online consumer review variables on interest in visiting café Naughty Little Cat Park. This study uses a type of quantitative research with an associative approach. Three hypotheses are proposed in this study. To test the three hypotheses, a questionnaire was distributed to 120 respondents. The analysis tool used in this study is SmartPLS. The tests carried out in this study include the outer model test which includes Individual Item Realism, Internal Consistency, Average Variance Extracted, and Discriminant Validity and the inner model test which includes Path Coefficient (β), R2 (Coefficient of Determination), t-test, f2 (Effect Size), and Q2 (Predictive Relevance). The results of this study show that 2 hypotheses are accepted, namely online consumer reviews affect brand knowledge and brand knowledge affects interest in visiting, but there is 1 hypothesis that is rejected, namely online consumer reviews affect interest in visiting.